Application and Effect Analysis of Formative Assessment in Cooperative Learning of Architectural Undergraduates - Wang, Ling (International Journal of Social Sciences and Public Administration, 2024)
In today’s education field, formative assessment has become a hot topic. This evaluation method can provide feedback for the teaching process and learning effect in time, so that teachers and students can make adjustments according to the actual situation. Especially in the cultivation of undergraduate students majoring in architecture, this evaluation method is particularly important. Architecture major requires students not only to have a solid theoretical foundation, but also to have good practical ability and teamwork spirit. Cooperative learning has been proved to be an effective teaching mode, which encourages students to learn from each other and help each other, thus improving teamwork ability, innovative thinking and problem-solving ability. The integration of formative assessment into cooperative learning can help students know their own learning situation in time, find out their shortcomings and adjust them in time. This study has deeply explored the practical application of formative assessment in cooperative learning for undergraduates majoring in architecture, hoping to provide strong theoretical support and practical direction for the educational model of architecture through detailed data and practical experience, and contribute to the architectural education in China.